THE â€œGreenâ€ TERM AND ACCOUNTING EDUCATION - Khairin, Fibriyani Nur; Sukoharsono, Eko Ganis; -, Roekhudin -; Hariadi, Bambang - (Accounting Department,, 2020)
AbstractPurpose â€“ This paper aims to uncover the meaning of